Biochemical profile and milk fat/protein in Saanen and Nubian goats - R.O.F. Prado; M.F. Valencia; R.J.A. Hernández; B.J.L. Zepeda; C.A.C. García (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT The biochemical profile and milk fats/proteins in Saanen and Nubian goats from Los Asmoles, Colima was carried out. Milk fat, milk protein, fat/protein ratio, glucose (GLU), cholesterol (COL), non-esterified fatty acids (NEFA), triacylglycerol (TAG), β-hydroxybutyrate (β-HBA), blood urea nitrogen (BUN), albumin (ALB), globulin (GLOB), total protein (PROT-T), calcium ion (Ca2+), inorganic phosphate (Pi), sodium ion (Na+), potassium ion (K+), magnesium ion (Mg2+), and chloride ion (Cl-) was calculated. The biochemical profile results were consistent with the international literature for goats. All analytes except ALB and β-HBA showed racial differences. The three milk variables registered a higher concentration in Nubian. The comparison between groups (high-yield vs. low-yield vs. dry period) showed differences in COL and β-HBA in both breeds. A negative correlation between GLU and NEFA was quantified. Positive correlations between NEFA with COL, TAG and β-HBA, between Ca2+ with Na+ and between K+ with Na+ and Mg2+ were quantified. Milk fat was correlated with COL, NEFA and β-HBA. Milk protein was correlated with BUN. The fat/protein ratio was correlated with COL and β-HBA. Results provide insight into metabolic adaptations in lactation and identify links between key analytes and milk fat/protein in goats.